HYBRID DATABASE APPLICATION - Mantovani, Pedro Henrique Nilson; Tiosso, Fernando (Revista Interface Tecnológica, 2020)
The purpose of this article is to provide an understanding of the operation of two types of databases that are currently widely used in e-commerce applications: relational and non-relational. In order to glimpse some scenarios and applications for these databases, it was necessary to review the concepts that permeate relational and non-relational databases, as well as to study the environment they support. In order to support the research, several publications were consulted involving the proposed objective, based on articles, documentation and books. For the practical development, an environment was used to manage the two types of databases, relational and non-relational, promoting a hybrid database scenario. With the experiments, it was possible to observe the results of the application, more specifically in relation to the storage of data in the two types of databases, highlighting characteristics such as security and performance, in addition to the emphasis on the use of JSONB data type, responsible for providing a differentiated performance in reading the data, justifying its possible use in e-commerce type applications.